Hydroxyl-ionic liquid functionalized metalloporphyrin as an efficient heterogeneous catalyst for cooperative cycloaddition of CO2 with epoxides. (August 2022) - Chen, Yupeng; Chen, Chong; Li, Xue; Feng, Nengjie; Wang, Lei; Wan, Hui; Guan, Guofeng
Abstract: Catalytic fixation of greenhouse gas CO2 into value-added chemicals under mild conditions was deemed as an effective pathway for carbon emissions mitigation, though facing big challenges. Herein, a novel hydroxyl-ionic liquid functionalized metalloporphyrin (ZnTpyp-IL) catalyst bearing hydrogen bond donor (HBD), Lewis acidic and nucleophilic sites was fabricated and invested in the CO2 cycloaddition without additive or solvent. The integration of ionic liquid endowed the framework with strong surface affinity to enrich CO2 molecules, while the cooperative interplay of multiple active sites further promoted the high-selective conversion of epichlorohydrin (ECH). Under optimal conditions (100 °C, 1 MPa, 4 h), the yield of corresponding chloropropene carbonate (CPC) reached 97.1 % (turnover frequency (TOF) = 52.4 h -1 ), far superior to that of bare Tpyp (17.4 %). The preliminary kinetic studies revealed the lower activation energy (59.54 kJ/mol) needed to be overcome in the ring-opening process over ZnTpyp-IL. Moreover, a plausible dual-activation mechanism of hydrogen bonds and Zn centers for epoxides was proposed based on the density functional theory calculation (DFT) to explain the acceleration of rate-determining step. Coupled with the satisfactory reusability and substrate expansibility, the developed ZnTpyp-IL demonstrated its great potential as robust heterogeneous catalyst in the efficient utilization of C1 resource. Graphical Abstract: ga1 Highlights: Heterogeneous ZnTpyp-IL catalyst was fabricated for cooperative CO2 fixation. Introduction of ionic liquid enhanced the surface affinity toward CO2 . Dual activation of Zn 2+ centers and -OH groups promoted ring-opening of epoxides. ZnTpyp-IL showed satisfactory catalytic activity, recyclability, and universality.